Perbandingan mutu tenaga pendidik di Indonesia dan Finlandia - Rasyida, Berliana (Maliki Interdisciplinary Journal, 2024)
Educators are one of the biggest factors in the development of education. Finland is one of the countries with the best education system, including in assuring the quality of its educators. With the condition of the quality of Indonesian educators who are still ranked 14th among developing countries, it is necessary to have a comparison as a measuring tool in improving the quality management of Indonesian educators. Therefore, this study aims to describe the quality management of educators in Finland and describe the improvement of quality management of Indonesian educators. The result of this research is that the quality assurance of educators in Finland starts from before the acceptance of prospective students to prospective teachers. The Indonesian government has also improved the quality of teaching staff with several programs, namely the driving teacher school, teacher professional education, and pembaTIK.